1964
DOI: 10.19182/remvt.7312
|View full text |Cite
|
Sign up to set email alerts
|

Les helminthes de quelques artiodactyles sauvages appartenant aux familles des bovidés et des suidés. Ces mammifères, en République du Tchad et en R.C.A., sont-ils des réservoirs de parasites pour les animaux domestiques vivant à leur contact?

Abstract: Les auteurs procèdent à l'autopsie d'une centaine de bovidés et suidés sauvages et identifient 47 espèces d'helminthes dont 26 spécifiques et 21 communes aux artiodactyles sauvages et domestiques (dont 13 très courantes, à large dispersion et fortement implantées dans le pays). Au Tchad et en R.C.A., les Artiodactyles sauvages ne paraissent pas - pour l'instant - représenter un danger certain pour les bovins, ovins, caprins ou camelins qui vivent à leur contact. Cependant, dans quelques cas - au demeurant limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

1969
1969
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 0 publications
1
10
0
2
Order By: Relevance
“…were present in antelopes at an infection rate of 75%, 41.4% in duikers, 100% in genet, 100% in pangolin, 50% in Cercopithecines (small monkeys), and 72.2% in porcupines. These results corroborate the work of several authors who have identified these parasites in antelopes, buffaloes, duikers, monkeys, and other wild mammals [ 19 , 20 , 21 , 22 ], confirming the fact that these parasite groups are herbivorous-mammalian gastrointestinal parasites [ 21 , 22 ]. Toxocara spp.…”
Section: Discussionsupporting
confidence: 91%
“…were present in antelopes at an infection rate of 75%, 41.4% in duikers, 100% in genet, 100% in pangolin, 50% in Cercopithecines (small monkeys), and 72.2% in porcupines. These results corroborate the work of several authors who have identified these parasites in antelopes, buffaloes, duikers, monkeys, and other wild mammals [ 19 , 20 , 21 , 22 ], confirming the fact that these parasite groups are herbivorous-mammalian gastrointestinal parasites [ 21 , 22 ]. Toxocara spp.…”
Section: Discussionsupporting
confidence: 91%
“…bothriophoron Defassa waterbuck Tanzania, Kenya Eduardo (1983) Cal. calicophorum African Buffalo, Blesbuck, Black wildebeest, Blue Wildebeest, Impala, Lelwel's hartebeest, Red hartebeest, Springbok South Africa, Uganda, DRC, Chad and Central African Republic Mettam (1932) ; Prudhoe (1957) ; Ortlepp (1961) ; Graber et al (1964) Cal. clavula African Buffalo, Bohor reedbuck, Common Eland, Defassa waterbuck, Impala, Oribi, Puku, Roan antelope, Red hartebeest, Sable Tanzania, Uganda, DRC, CAR, Republic of Niger, Nigeria, Sudan Stunkard (1929) ; Nasmark (1937) ; Prudhoe (1957) ; Dinnik et al (1963) ; Sey and Graber (1979a) ; Eduardo (1983) Dinnik et al (1963) Cal.…”
Section: Resultsmentioning
confidence: 99%
“…daubneyi East African oryx Ethiopia Graber et al (1980) Cal. microbothrium African Buffalo, Blesbok, Bohor reedbuck, Common Eland, Defassa Waterbuck, Impala, Kob, Lelwel hartebeest, Red hartebeest, Red lechwe, Roan Antelope, Senegal hartebeest, Waterbuck South Africa, Zambia, Zimbabwe, Tanzania, Kenya, Uganda, Chad, CAR, Ghana, Sudan, Egypt, Botswana Maplestone (1923) ; Baer (1923) ; Mettam (1932) ; Myers et al (1960) ; Ortlepp (1961) ; Graber et al (1964) ; Sey (1977) ; Eduardo (1983) ; Halium et al (2014) Cal. phillerouxi African Buffalo, Bohor reedbuck, Deffasa Waterbuck, Greater Kudu, Impala, Kob, Topi, Common Eland, Hartebeest, Thomson's gazelle Zambia, Uganda, Zimbabwe, Tanzania, DRC, CAR Dinnik et al (1963) ; Sachs and Sachs, 1968 ; Sey and Graber (1979a) ; Eduardo (1983) ; Cal.…”
Section: Resultsmentioning
confidence: 99%
“…Autores como Graber et al (1964), Prestwood et al (1975, 1976) e Nascimento (2004, comentam sobre as possibilidades de infecções cruzadas de helmintos entre espécies de animais silvestres e domésticos. Graber et al (1964), ao estudarem Bovidae e Suidae silvestres, encontraram 47 espécies de helmintos, das quais 26 necessitam de hospedeiro específico e 21 são comuns aos animais domésticos e silvestres, levando os autores a questionarem o potencial destes animais silvestres como reservatórios de parasitos para animais domésticos que convivem no mesmo ambiente.…”
Section: Resultsunclassified
“…Graber et al (1964), ao estudarem Bovidae e Suidae silvestres, encontraram 47 espécies de helmintos, das quais 26 necessitam de hospedeiro específico e 21 são comuns aos animais domésticos e silvestres, levando os autores a questionarem o potencial destes animais silvestres como reservatórios de parasitos para animais domésticos que convivem no mesmo ambiente.…”
Section: Resultsunclassified